Enzyme-assisted peptide folding, assembly and anti-cancer properties. Issue 33 (9th August 2017) - Liang, Chunhui; Zheng, Debin; Shi, Fang; Xu, Tengyan; Yang, Cuihong; Liu, Jianfeng; Wang, Ling; Yang, Zhimou
Abstract : Enzymatically triggered reactions provide a unique pathway to produce α-helical peptides and hydrogels. Abstract : The α-helix is the most prevalent conformation in proteins. However, formation of the α-helical conformation remains a challenge for short peptides with less than 5 amino acids. We demonstrated in this study that enzyme-instructed self-assembly (EISA) provides a unique pathway to assist the self-assembly of peptides into the α-helical conformation, while a heating–cooling process leads to a conformation more similar to a β-sheet. The same peptide with different conformations self-assembled into different nanostructures. The peptide with α-helical conformation self-assembled into stable nanofibers and hydrogels, while the other one assembled into an unstable nanoparticle suspension. The nanofiber solution exhibited better stability against proteinase K digestion and an enhanced cellular uptake compared to the nanoparticle solution. Therefore, the nanomedicine formed by the α-helical peptide showed a better inhibition capacity against cancer cells in vitro and significantly inhibited tumor growth in vivo compared to the one formed by the β-sheet peptide. Our study demonstrates the unique advantages of EISA to assist peptide folding and self-assembly into biofunctional nanomaterials.